Nonlinear interaction of 3‐D kinetic Alfvén wave and fast magnetosonic wave. Issue 8 (27th August 2014) - Sharma, Prachi; Yadav, N.; Sharma, R. P.
Abstract The nonlinear interaction of 3‐D kinetic Alfvén wave and fast magnetosonic wave for the intermediate‐β plasma in magnetopause has been considered in the present study. A set of dimensionless equations has been derived taking ponderomotive nonlinearity into account due to kinetic Alfvén wave in the fast magnetosonic wave dynamics. In order to analyze the nonlinear coupling of fast magnetosonic wave and kinetic Alfvén wave and also to study its effect on the turbulent power spectrum, we have numerically solved these coupled equations using pseudo‐spectral method of simulation. The results show the appearance of localized structures of kinetic Alfvén wave, which may be accountable for the heating and acceleration of plasma. The obtained results are consistent with the recent observations by Time History of Events and Macroscale Interactions during Substorms spacecraft in magnetopause.